Analisis Pengendalian Internal Dalam Pemberian Kredit Pada PT Bank Perkreditan Rakyat (BPR) Indomitra Mandiri - Wijoyo, Hadion (TIN: Terapan Informatika Nusantara, 2020)
Credit crunch is a matter that causes difficulties for the bank itself, namely in the form of difficulties, especially those concerning the soundness of banks, therefore banks are required to avoid bad loans. The emergence of credit arrears is influenced by several factors, but in this study only limited to internal control factors that still refer to Character, Capacity, Capital, Collateral and Condition. Analysis of the data used is descriptive method, namely analyzing the realities that are found in the field, then linking them with theories that the author has obtained, so that a conclusion can be drawn which is a solution to the problem at hand. The creditors are not good enough in analyzing the habits of prospective customers. The creditor in giving credit does not do the 5C principles properly and is committed to running in a whole way. Inappropriate policies, especially in the provision of loans without collateral, because customers in returning loans are still too often too late for various reasons.